733 Bacterial 16S R RNA Genetic Markers for Fecal Samples to Differentiate Choledochal Cyst from Biliary Atresia. (October 2012) - Okada, T; Honda, S; Miyagi, H; Taketomi, A
Abstract : Background and Aims: Microbiota in fecal content from choledochal cyst (CC) and biliary atresia (BA) individuals at the operation were compared using 16S rRNA gene libraries and terminal restriction fragment length polymorphism (T-RFLP). Methods: From 2002 to 2011, 1 infant with CC and 7 infant with BA (infants ≤ 2 months of age) were treated at our institute. Fecal samples were obtained at the radical operation for CC and BA. Total fecal DNA was isolated and PCR was performed. The amplification of the fecal 16S rDNA, restriction enzyme (BslI), size-fractionation of T-RFs and T-RFLP data analysis were performed. To compare the T-RFLP patterns among samples between CC and BA patients, the dissimilarity index which indicate the percentage of the peak area of the fragment (operational taxonomic unit: OTU) was used. Results: Two fecal samples of 1 CC infant and 14 fecal samples of 7 BA infants were obtained. Nine predominant OTUs were detected with Bsl I digestion. The microbiota consisted of microbial communities of Bifidobacterium, Lactobacillales, Bacteroides, Prevotella, Clostridium clusters IV, XI, and XVIII, and Clostridium subcluster XIVa. The Bifidobacterium, Bacteroides, and Clostridium clusters were detected predominatly in CC than BA group. Lactobacillales was most predominat group in BA feces. Conclusions: Bacterial DNA showed marked differences in the composition of fecal microbiota in CC and BA infants. Molecular analysis of colonic microbiota using 16S rRNA gene libraries and T-RFLP might be useful to differentiate CC from BA.